The practical use of inconsistency information in engineering design tasks - first observations. (2017) - Sadlauer, Alfred; Riedl-Ehrenleitner, Markus; Hehenberger, Peter; Demuth, Andreas; Egyed, Alexander
Today's product development projects require collaboration across different engineering domains in order to be successful. For instance, a project may require software engineers to collaborate with electrical engineers and mechanical engineers. Even though engineers of different domains focus on different parts of the system-under-development, these parts typically cannot work in isolation. Therefore, coordination among these engineers is necessary to ensure that the individual parts of a system work together well when combined. The lack of such coordination leads to inconsistencies and hence the inability to integrate individual parts of the system. Even though approaches for finding such inconsistencies have been developed, it has yet to be shown whether the presentation of inconsistencies is of actual value to engineers. In this paper, we present the results of a practical experiment that assessed the effects of the presence of inconsistent information during development. The results indicate that specific feedback about inconsistency (when performing changes) leads to better engineering results than merely presenting general information about system interconnections.